THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE MEDIATED BY WORK STRESS STUDY ON EMPLOYEES OF BANK BRI KC MALANG KAWI - Ardhita Widyadhana; Noermijati; Christin Susilowati (CV. Radja Publika, 2023)
In the contemporary landscape of globalization, the heightened competitiveness within the banking industry emerges as a pivotal determinant influencing a firm's attainment of its objectives. To thrive in this fiercely competitive environment, human resources emerge as a paramount factor with the potential to drive all facets of organizational operations. Hence, it becomes imperative for the banking sector to nurture a workforce that demonstrates outstanding performance in the execution of company activities. The primary objective of this research is to examine the impact of transformational leadership and the work environment on employee performance, mediated by the variable of work stress. The study population encompasses all employees of Bank KC Malang Kawi, totaling 116 individuals. The research sample consists of the entire population, encompassing all employees at Bank BRI KC Malang Kawi. Data collection methods employed in this study encompass questionnaires and documentation. The data analysis method involves the use of Partial Least Squares (PLS). The findings of this research demonstrate that both transformational leadership and the work environment exert an influence on employee performance. Additionally, work stress is identified as a partial mediator between transformational leadership and the work environment in relation to employee performance.